2004
DOI: 10.1080/10929080500165476
|View full text |Cite
|
Sign up to set email alerts
|

The use of a head-mounted display for visualization in neuroendoscopy

Abstract: The HMD is a new visualization tool in neurosurgery that may improve the ergonomics of neuroendoscopic and endoscope-controlled procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 11 publications
0
23
0
Order By: Relevance
“…Optical see-through HMDs allow the user to view the real world through a semitransparent mirror, thereby enabling the superimposition of electronic text or images over the user's natural view, while video see-through HMDs feature non-transparent screens that instead display a video feed of a real-world scene, captured with an external camera, in front of the user's eyes 88. The use of video HMDs was described in all 20 articles pertaining to MIS where HMDs provided users with an individualised endoscopic display 44 49 51–54 56–58 64 65 69 72 80 81 83–87…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Optical see-through HMDs allow the user to view the real world through a semitransparent mirror, thereby enabling the superimposition of electronic text or images over the user's natural view, while video see-through HMDs feature non-transparent screens that instead display a video feed of a real-world scene, captured with an external camera, in front of the user's eyes 88. The use of video HMDs was described in all 20 articles pertaining to MIS where HMDs provided users with an individualised endoscopic display 44 49 51–54 56–58 64 65 69 72 80 81 83–87…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-three of the 45 articles (73%) describing the use of HMDs were primary research articles, 19 of which were exploratory studies carried out in clinical settings 47 49 51 52 55–58 65 66 69 71 80 81 83–87. Device design and methodology varied significantly across these studies, but the results overall demonstrated the feasibility of HMDs in the various specified clinical environments.…”
Section: Resultsmentioning
confidence: 99%
“…The endoscopic picture is projected onto LCD screens from the HMD with a resolution of 800 × 600 pixels [6]. The instruments used are principally the same as with the microsurgical technique.…”
Section: Methodsmentioning
confidence: 99%
“…However, in head-up microscopy, a surgeon's head and eyes are directed toward a monitor, which causes an eye-hand coordination mismatch and requires an uncomfortable posture for surgeons. Head-mounted displays (HMDs) have been adopted to solve the above mentioned drawbacks in the case of endoscopy and laparoscopy, which use the same kinds of 3D monitors [6][7][8][9][10][11][12][13]. The use of HMD helps eliminate these problems by delivering optical information directly to the surgeon's eyes, independent of the head and body position and the position of the sources of the images.…”
Section: Introductionmentioning
confidence: 99%
“…Many of proposed HMDs have inadequate resolution, and they are bulky, cave-like, and heavy [6][7][8][9][10]. Although, a higher resolution HMD have recently been proposed for endoscopy, it has a fully opaque and closed, non-see-through configuration [11][12][13].…”
Section: Introductionmentioning
confidence: 99%